Paradoxical response in a patient with non-small cell lung cancer who received nivolumab followed by anti-Mycobacterium tuberculosis agents. Issue 1 (January 2019) - Takata, So; Koh, Genju; Han, Yuki; Yoshida, Hiroko; Shiroyama, Takayuki; Takada, Hiromune; Masuhiro, Kentarou; Nasu, Shingo; Morita, Satomu; Tanaka, Ayako; Hashimoto, Syouji; Uriu, Kiyoaki; et al.
Abstract: Anti-programmed cell death-1 (PD-1) agents enhance the antitumor immunoresponse. A number of reports have indicated that patients with malignancies who receive anti-PD-1 agents are at risk for tuberculosis (TB) infection. In this report, we present a patient with non-small cell lung cancer who developed pulmonary tuberculosis while receiving the anti-PD-1 agent nivolumab, and who subsequently demonstrated a paradoxical response (PR) 10 days after initiation of anti-MTB treatment. We suggest that anti-PD-1 agents not only induce the development of pulmonary TB, but also development of PR after anti-MTB treatment, through upregulation of the immune response. Furthermore, based on their radiological and immunological similarity, we speculate that the schema of development of PR closely resembles that of pseudoprogression in non-small cell lung cancer patients after anti-PD-1 treatment.